Concurrent Tumors Revealed by an Autopsy-A Case Report and Literature Review - Miruna Cristian; Mădălina Boșoteanu; Mariana Așchie; Angelica Potamian; Cătălin Adrian Boșoteanu; Gabriela Izabela Bălțătescu (Case Reports in Gastrointestinal Medicine, 2022)
Introduction. Multiple primary malignant neoplasms are an uncommon phenomenon, given the very low incidence of two or more different tumors, while neoplasm may be limited to a single organ or may involve multiple separate anatomical organs. The main purpose of this study is to highlight the importance of morphological and immunohistochemical tests to distinguish the origin of the primary tumor. Case Presentation. We report the case of a 65-year-old deceased male, presenting multiple tumors in the lung, stomach, kidneys, and adrenal organs. The main symptoms presented by the patient were dyspnea with a range of 77% with oxygen saturation, fatigability, and productive cough. Histopathological examination revealed a solid and papillary lung adenocarcinoma, concurrent with tubular gastric adenocarcinoma. Immunohistochemical testing was mandatory by using a panel of seven monoclonal mouse antibodies (TTF-1, Napsin A, CK7, CK20, p40, synaptophysin, and chromogranin A). The pulmonary tumoral immunophenotype (positive for TTF-1, Napsin A, CK7; negative for CK20, p40, synaptophysin, and chromogranin A) confirms the diagnosis of primary lung ADC and invalidates the hypothesis of a metastasis arisen from a gastric adenocarcinoma or other forms of lung cancer. Conclusion. The importance of the ancillary test is to distinguish a primary tumor from a metastatic one.